Réponses

2013-01-19T16:45:58+01:00

Bonjour,

 

On prend :

a=99 997

 

Donc, ton expression peut s'écrire :

a^2-(a+2)(a+1)

On déveolppe :

a^2-a^2-3a-2\\ -3a-2\\ -3\times 99997-2 = -299993

2013-01-19T17:07:49+01:00

par les identités remarquables
99997² = (100000-3)² = 100000²- 2*3*100000 +3²
99 999 x 99 998 = (100000-1)*99 998 = 99 998*100000 - 99 998 = 100000² -2*100000 - 99998
reste
=100000²- 2*3*100000 +3² - 100000² +2*100000 + 99998
=-4*100000 +99998 +9
=-300002+9
=−299993

 

voila ^^